Children Change Their Answers in Response to Neutral Follow‐Up Questions by a Knowledgeable Asker - Bonawitz, Elizabeth (Cogn Sci, 2020)
Burgeoning evidence suggests that when children observe data, they use knowledge of the demonstrator's intent to augment learning. We propose that the effects of social learning may go beyond cases where children observe data, to cases where they receive no new information at all. We present a model of how simply asking a question a second time may lead to belief revision, when the questioner is expected to know the correct answer. We provide an analysis of the CHILDES corpus to show that these neutral follow‐up questions are used in parent–child conversations. We then present three experiments investigating 4‐ and 5‐year‐old children's reactions to neutral follow‐up questions posed by ignorant or knowledgeable questioners. Children were more likely to change their answers in response to a neutral follow‐up question from a knowledgeable questioner than an ignorant one. We discuss the implications of these results in the context of common practices in legal, educational, and experimental psychological settings.